Tratamiento contable de la propiedad, planta y equipo de la constructora Chanpal S.A. en el periodo 2020 - Victorio Delgado, Jefferson David (2021)
Properties, plant, and equipment are tangible components with specific characteristics, which a company has for use in the realization or supply of goods or services, to rent them to third parties or for administrative purposes. It is estimated that they are used over more than one accounting cycle. This case study provides important information regarding the accounting treatment of the property, plant and equipment of the construction company “Chanpal S.A” in the city of Babahoyo in the province of Los Ríos. This research is supported by key and relevant information in relation to the treatment of the property, plant, and equipment account. This case study was born from the concern expressed by entrepreneurs in demonstrating the correct accounting treatment of fixed assets, which are acquired and necessary to perform adequate tasks in each company. In addition, it was designed with the aim of contributing important information to the correct treatment and registration of the aforementioned account, in addition to incorporating the observation of the accounting records whose purpose is to confirm that the information is effective, valid and reliable.